Religiusitas Tradisi Hudoq - Dayak Bahau dan Krisis Ekologis dalam Perspektif Laudato Si - Meko , Agustinus Masterinus Laka; Lestari, Nani Indah (Perspektif, 2022)
This study examines the relationship between ecology and the religious identity of the Dayak Bahau people in the Hudoq. Between humans and nature, there is an inseparable link. When we talk about the Dayak people, at the same time we are talking about nature. It is from nature that the Dayak Bahau people find their identity. When modernism enters and pervades development that is not environmentally friendly, an ecological crisis occurs. A crisis of identity and meaning ensued. The methodology of this research is a literature review by reading, describing, analyzing and making implicative reflections. The purpose of this research firstly is to invite everyone, in particular, to return and search for identity in local culture, in the context of Hudoq. On the other hand, from the perspective of Laudato Si the Apostolical Letter of Pope Francis, life transformation is needed when dealing with the development of science and technology which is often misused to exploit nature and human culture. All people are invited to build a life of integrity, namely knowing their identity and growing in prosperity.